2013
DOI: 10.1590/s0100-69162013000600008
|View full text |Cite
|
Sign up to set email alerts
|

Changes in water availability in the soil due to tractor traffic

Abstract: Frequent traffic of tractors in agricultural soils, promotes soil compaction and affects the flow and water availability. The aim of this research was to study the effect of compaction induced by tractor traffic on water availability in the soil under different traffic intensities on the same path (0, 1, 3, 6 and 10 passages), to two tractors with 3.3 and 2.6 ton of weights, over three different surface conditions. The study was conducted in an Andisol, representative soil of the study area. It was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…While Bowen et al (1994) identified critical values that ranges between 0.9 and 1.5 MPa for root growth, soils possessing a PR closer to 2.0 MPa were classified as having excessive compaction (Leao and Silva, 2006). Such compaction influences roots penetration through the soil (Chan et al, 2006;Hakansson and Lipiec, 2000;Hamza and Anderson, 2005), favors run-off and the accumulation of water on the surface due to a reduced number of porous spaces and the formation of a relatively impermeable surface layer (Islam et al, 2011;Gómez-Rodríguez et al, 2013).…”
Section: Descriptive Analysis Of Soil Penetration Resistancementioning
confidence: 99%
“…While Bowen et al (1994) identified critical values that ranges between 0.9 and 1.5 MPa for root growth, soils possessing a PR closer to 2.0 MPa were classified as having excessive compaction (Leao and Silva, 2006). Such compaction influences roots penetration through the soil (Chan et al, 2006;Hakansson and Lipiec, 2000;Hamza and Anderson, 2005), favors run-off and the accumulation of water on the surface due to a reduced number of porous spaces and the formation of a relatively impermeable surface layer (Islam et al, 2011;Gómez-Rodríguez et al, 2013).…”
Section: Descriptive Analysis Of Soil Penetration Resistancementioning
confidence: 99%
“…Past research also focused on the investigation of the impacts of land use change/management on the water retention capacity of Andosols. The land use change or management practices included crop and agroforestry (Abera & Wolde‐Meskel, 2013), crop rotation (Duwig et al, 2019), overgrazing (Buytaert, Wyseure, et al, 2005; Podwojewski et al, 2002), forest/wetland conversion to grassland (Dec et al, 2017; Dörner et al, 2016; Roa‐García, Brown, Schreier, & Lavkulich, 2011), native forest or grassland conversion to pasture, exotic forest, or crops (Daza Torres, Hernández Flórez, & Triana, 2014; Dörner, Dec, Peng, & Horn, 2009b, 2010; Farley, Kelly, & Hofstede, 2004; Marín et al, 2018; Quichimbo et al, 2012), soil compaction due to tractor traffic (Gómez‐Rodríguez, Camacho‐Tamayo, & Vélez‐Sánchez, 2013), and biosolid application (Salazar et al, 2012). Our findings indicate that although the results from such evaluations are valid for the wetter portion of the WRC (from saturation to pF ~ 1.7), they should be used with caution for the drier range of the curve.…”
Section: Discussionmentioning
confidence: 99%
“…Forest substitution in PPAs in the basin drain ing the upper Marrecas River valley by anthropic uses increases surface runoff and soil losses by reducing evapotranspiration, vegetation interception, protection caused by roots, among others (Githui et al, 2009;Zhang et al, 2015;Eu m et al, 2016;Silva et al, 2016b;Lot z et al, 2017). The current agricultural cult ivation, which is the main substitute for forest cover, compacts soil horizons mainly due to agricu ltural machinery traffic , reducing infiltrat ion rates and increasing soil bulk density (Ankeny et al, 1990, Abu-Hamdeh, 2003Gó mez-Rodríguez et al, 2013, Feitosa et al, 2015Silva et al, 2016a).…”
Section: Res Ults and Discussionmentioning
confidence: 99%